1995
DOI: 10.1007/bf00189297
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of a sphere behind planar shock waves

Abstract: Experiments in Fluids zo (1995) 84 90 ~' Springer-Verlag 1995 planar shock waves 84 Abstract The paper presents the results of an investigation on the motion of a spherical particle in a shock tube flow. A shock tube facility was used for studying the acceleration of a sphere by an incident shock wave. Using different optical methods and performing experiments in two different shock tubes, the trajectory and velocity of a spherical particle were measured. Based upon these results and simple one-dimensional cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Dealing with the transient evolution of the shock wave reflection Shock wave reflection over a coupled convex-concave cylindrical surface 221 and related physical phenomena, one must employ very fast high-resolution imaging systems (Skews 2008). Over recent decades, studies in this field have dealt with a variety of problems such as: shock wave reflections from blunt objects including cylinders (Sun et al 2003;Skews & Kleine 2010;Glazer et al 2011;Kleine et al 2014), spheres (Britan et al 1995;Tanno et al 2003) and porous plates (Skews 2005); shock focusing (Johansson, Apazidis & Lesser 1999;Bond et al 2009;Skews & Kleine 2010) and the RR → MR and MR → RR transitions (Skews & Kleine 2007;Geva et al 2013;Gruber & Skews 2013). Some of these studies utilized high-speed photography with capturing rates ranging from a few thousand up to one million of frames per second (f.p.s.).…”
Section: Methodsmentioning
confidence: 99%
“…Dealing with the transient evolution of the shock wave reflection Shock wave reflection over a coupled convex-concave cylindrical surface 221 and related physical phenomena, one must employ very fast high-resolution imaging systems (Skews 2008). Over recent decades, studies in this field have dealt with a variety of problems such as: shock wave reflections from blunt objects including cylinders (Sun et al 2003;Skews & Kleine 2010;Glazer et al 2011;Kleine et al 2014), spheres (Britan et al 1995;Tanno et al 2003) and porous plates (Skews 2005); shock focusing (Johansson, Apazidis & Lesser 1999;Bond et al 2009;Skews & Kleine 2010) and the RR → MR and MR → RR transitions (Skews & Kleine 2007;Geva et al 2013;Gruber & Skews 2013). Some of these studies utilized high-speed photography with capturing rates ranging from a few thousand up to one million of frames per second (f.p.s.).…”
Section: Methodsmentioning
confidence: 99%
“…Because of the importance of problems of shockwave propagation in dust-gas mixtures, a large number of publications on the aerodynamic drag C x of spherical particles in flows behind shock waves have appeared during the last decade [9][10][11][12]. It was found that the value of C x under these conditions is significantly (severalfold) higher than in the case of a steady flow, though the global tendency of a slight decrease in C x with increasing Reynolds number Re is the same as in steady events (at least, in the range 10 3 < Re < 10 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, Fig. 3b shows that for most of the time the particle Reynolds number may be greater than one suggesting that (equations (7, 9)) are a safer representation for the viscous force than the simple Stokes analysis [34]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For particle Reynolds numbers ( Re p ) Rep=ρvf(r,t)vp(r,t)Dμ greater than one (a typical maximum value of Re p in our experiment is ~30), the radial component of the viscous force F vis_r acting on a completely immersed particle in a uniform liquid velocity field is [34] Fvis_r=π4D2ρCd12vf(r,t)vp(r,t)(vf(r,t)vp(r,t)) where the fluid velocity v f depends on radial position, r , time, t, and the particle velocity, v p is also a function of r and t . Equation (7) does not include unsteady forces acting on the particle.…”
Section: Forces Acting On a Partially Wetted Particle At An Interfacementioning
confidence: 99%